Granuloma coinfection with Mycobacterium bovis, Mycobacterium avium subsp. paratuberculosis, and Corynebacterium pseudotuberculosis in five hunted red deer (Cervus elaphus) in Portugal - Matos, A.C. (2016)
Submitted by Ana Matos (acmatos@ipcb.pt) on 2016-03-05T01:29:18Z No. of bitstreams: 1 jwdi-51-03-793-794-e_003.pdf: 112851 bytes, checksum: 6d9be3b4370763721c54efad9b8d1b15 (MD5)